PENDIDIKAN KESEHATAN DAN PENERAPAN ALAT PELINDUNG DIRI DALAM UPAYA PENCEGAHAN LEPTOSPIROSIS DI DESA SELANDAKA, KECAMATAN SUMPIUH KABUPATEN BANYUMAS - Dwi Sarwani Sri Rejeki; Sri Nurlaela; Devi Oktaviana (Kesmas Indonesia, 2015)
ABSTRACTIndonesia is an endemic country to the Leptospirosis. It is known that Banyumas regency is attacked by leptospirosis for the first time since several years ago. These two years show that the incidents are increasing and it needs an action so it can be well treated and the extraordinary case will not happen. The research shows that Leptospirosis happens in the area closed to the rice field and river. Selandaka village was the highest number of incident in 2010-2013 (38.5%) Banyumas regency. Most of the villagers are farmers or labor for the farmer (90%). These jobs have more changes to suffer from Leptospirosis. Most of the sufferers are male (76.9%) and at the age of 22 years. It is caused by their habit not to use Personal Protective Equipment (PPE). The research was aimed to improve the awareness of PPE to farmers. It was done through the counseling, training, companionship, and installation of information board. The counseling was done at 30 Mei 2014 and the training was at 4 June 2014. The research showed that the average knowledge before the counseling was 14.80 and improved to be 18.04 or 21.83%. The average score to the attitude before the treatment was 31.00 and improved to be 32.61 or 5.2%. The companionship found that the improvement of obedience level to PPE installation. In the 4 companionship, it showed that the obedience of the farmers was 100% to the use of boot shoes, 85% to the use of gloves and those farmers were sometimes used 15%. It was expected that the farmers who joined the activities could promote the information about leptospirosis as well as the prevention to other farmers.Keywords: Leptospirosis, Personal Protective Equipment, farmers Kesmasindo, Volume 7( 2) Januari 2015, Hal. 118-131